PENERAPAN SOP TERHADAP KESELAMATAN KERJA DI SPBU (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study seeks to examine the application of written operational guidelines in relation to occupational safety within gas station environments (SPBU). Such workplaces are classified as high-risk areas due to their susceptibility to fires, explosions, and exposure to hazardous materials. Consequently, strict adherence to these operational directives plays a crucial role in minimizing workplace accidents. The research adopts a descriptive quantitative design, gathering data through questionnaires distributed to gas station operators and field observations regarding the execution of operational protocols.The results reveal that consistent implementation of these guidelines significantly enhances workplace safety, particularly in accident prevention, the proper use of personal protective equipment (PPE), and operator vigilance in identifying potential hazards. Moreover, the existence of these structured procedures contributes to a more orderly working atmosphere, reduces human errors, and strengthens customer safety. Nevertheless, several challenges remain, including insufficient managerial oversight, low employee awareness, and limited availability of safety equipment at certain stations. Therefore, these operational frameworks should not merely function as formal documents but need to be embedded into the organizational culture to sustain long-term workplace safety.